Regulation of adhesion behavior of murine macrophage using supported lipid membranes displaying tunable mannose domains - Kaindl, Thomas; Kaufmann, Stefan; Engel, Ulrike; Tanaka, Motomu (Journal of physics. Condensed matter, 2010)
Highly uniform, strongly correlated domains of synthetically designed lipids can be incorporated into supported lipid membranes. The systematic characterization of membranes displaying a variety of domains revealed that the equilibrium size of domains significantly depends on the length of fluorocarbon chains, which can be quantitatively interpreted within the framework of an equivalent dipole model. A mono-dispersive, narrow size distribution of the domains enables us to treat the inter-domain correlations as two-dimensional colloidal crystallization and calculate the potentials of mean force. The obtained results demonstrated that both size and inter-domain correlation can precisely be controlled by the molecular structures. By coupling α-D-mannose to lipid head groups, we studied the adhesion behavior of the murine macrophage (J774A.1) on supported membranes. Specific adhesion and spreading of macrophages showed a clear dependence on the density of functional lipids. The obtained results suggest that such synthetic lipid domains can be used as a defined platform to study how cells sense the size and distribution of functional molecules during adhesion and spreading.